Nouns of Lithuanian Slang with the Slavic suffixes: Borrowings and Hybrids - Kudirka, Robertas (Verbum, 2022)
The article analyses 200 nouns of Lithuanian slang with the three most common Slavic suffixes: -ka, -kė (Russ. -ка, Pl. -ka); -akas (Russ. -ак, Pl. -ak), -iakas (Russ. -як); -ščikas, -čikas (Russ. -щик, -чик). The majority of nouns in the slang are with the suffixes -kė, -ka. A part of the borrows with theses suffixes are the result of suffix univerbation; the univerbs usually are informal or slang words in Russian language. The borrowings with the suffixes -akas, -iakas are the second most common: these nouns are mostly slang words in Russian. There are many hybrids created with the suffixes -akas, -iakas in Lithuanian slang. The nouns with the suffixes -ščikas, -čikas are the third most common; the words with -ščikas are more ordinary in slang; the suffix -čikas is less common, but both forms are often used as synonyms. There are also few pseudo-borrowings with Russian roots and suffixes -ščikas, -čikas as well as hybrid derivatives.